CT-based investigation of the contraction of ex vivo tissue undergoing microwave thermal ablation. (7th March 2018) - Lopresto, Vanni; Strigari, Lidia; Farina, Laura; Minosse, Silvia; Pinto, Rosanna; D'Alessio, Daniela; Cassano, Bartolomeo; Cavagnaro, Marta
Abstract: Treatment planning in microwave thermal ablation (MTA) requires the capability to predict and estimate the shape and dimension of the thermally coagulated zone obtainable following a clinical protocol. The ultimate result relies on the knowledge of the performance of the ablation device, as well as of the temperature-dependent structural modifications that the tissue undergoes during the treatment, because of the very high temperatures reached (up to 100 °C or higher). In this respect, tissue shrinkage plays an important role, since the dimension of the ablated tissue evaluated at the end of the MTA procedure (e.g. by way of CT imaging) could underestimate the actual treated tissue, leading to inaccurate assessment of the treatment outcome. In this study, CT imaging was used for real-time monitoring of tissue contraction during MTA experiments carried out in ex vivo bovine liver. Fiducial lead markers were positioned into the tissue in a 3D spatial grid around the MTA applicator. The spatial and temporal evolution of tissue contraction was imaged during the experiments, and analysed in terms of displacements of clusters of fiducial markers. The results obtained indicated that contraction is highly heterogeneous in the zone of ablation, depending both on the heating and on interactions with nearby tissue. In particular, tissue shrinkage appeared asymmetric with respect to the direction of insertion of the microwave applicator in the central area of carbonised tissue (about 30% and 19% along the radial and longitudinal directions, respectively), and isotropic in the region of coagulated (but not carbonised) tissue (about 11%). The total ablated volume was reduced by approximately 43% with respect to its pre-ablation value. Finally, temperature measurements displayed a correlation between temperature increment and temporal evolution of tissue contraction in the zone of ablation.